2008
DOI: 10.7326/0003-4819-148-10-200805200-00006
|View full text |Cite
|
Sign up to set email alerts
|

Association of Numeracy and Diabetes Control

Abstract: Poor numeracy skills were common in patients with diabetes. Low diabetes-related numeracy skills were associated with worse perceived self-efficacy, fewer self-management behaviors, and possibly poorer glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
351
1
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(383 citation statements)
references
References 25 publications
25
351
1
6
Order By: Relevance
“…Health numeracy refers to 'the degree to which individuals have the capacity to access, process, interpret, communicate, and act on numerical, quantitative, graphical, biostatistical, and probabilistic health information needed to make effective health decisions' [9]. Patients with a low level of numeracy have a lower ability to perform a number of tasks required for their treatment, such as carbohydrate counting, identification of self-monitored blood glucose values within the target range and adjustment of insulin doses [10].…”
Section: In Hismentioning
confidence: 99%
“…Health numeracy refers to 'the degree to which individuals have the capacity to access, process, interpret, communicate, and act on numerical, quantitative, graphical, biostatistical, and probabilistic health information needed to make effective health decisions' [9]. Patients with a low level of numeracy have a lower ability to perform a number of tasks required for their treatment, such as carbohydrate counting, identification of self-monitored blood glucose values within the target range and adjustment of insulin doses [10].…”
Section: In Hismentioning
confidence: 99%
“…Data in adults with diabetes has found that low health literacy has been associated with less diabetes knowledge (DeWalt, Boone, & Pignone, 2007) poorer diabetes selfcare (Cavanaugh et al, 2008), worse diabetes control (Powell, Hill, & Clancy, 2007) and a 2-fold increase in retinopathy complication (Schillinger et al, 2002).…”
Section: Association Of Health Literacy and Health Outcomesmentioning
confidence: 99%
“…16,17 More research is emerging, which demonstrates that one's cognitive abilities, as measured by executive functioning (i.e., the ability to regulate behavior, metacognition, and cognitive autonomy) also play a role in successful diabetes self-care, beyond the influence of youth age. 16,18 Diabetes numeracy, the numerical skills needed to complete diabetes self-management tasks, has also been found to be related to improved diabetes knowledge, self-efficacy, and glycemic control in adults, 19 yet this body of research needs to be extended to youth with type 1 diabetes.…”
Section: Individualmentioning
confidence: 99%